TR1 Virtual reality fully immersive interactive technology. Can this enhance simulation training and reduce skill fade?. (November 2018) - Judd, Thomas; Cook, Nicola; Hunter, Ian
Abstract : Background: Recent technology advancements allow a smartphone to be converted into a virtual reality headset. We have developed a method of Virtual Reality Fully Immersive Interactive Technology Teaching (VR FIITT) where a student may be fully immersed in a virtual reality teaching scenario. This technology has the potential to limit skill fade once a simulation course has been delivered. Simulation courses are difficult to deliver due to time pressure on faculty, students and staff. This along with the cost of running these courses means skill fade (especially for resuscitation skills) is a real problem, with most practitioners losing their skills within 3 months1. The aim of this research is to see if a blended course of hospital life support (HLS) training plus VR FIITT can improve resuscitation training, and address the issue of skill fade of resuscitation skills. Methodology: 24 preclinical medical students that have not received any life-support training will be recruited. They will then be randomised into two groups. The first group will be the control and receive standard HLS training. The second group will be the intervention group and will have access to VR FIITT on their phones to view as many times as they wish alongside the standard HLS course. After the training, all students will undergo a simulation that will test the elements taught in the HLS course. Time taken for key interventions to be carried out will be measured. A follow up simulation will be done after 3 weeks. Where the control group will have had no further training, and the intervention group will have had unlimited access to the VR FIITT. We will then retest the students with another HLS scenario and measure the same outcomes to see if there is a difference between the two groups. Results: The hypothesis is that the students with access to VR FIITT will perform better in the test scenario. We expect to see less of a decline in test scores in the intervention group when they are retested 3 weeks later. Data collect is currently on going, and will finish in June 2018. Discussion and conclusion: This research project hopes to show that in this fast-growing field, VR will have an ever more important role alongside/replacing simulation. With ever more increasing clinical pressures and difficulty for clinical staff to keep up competency based training, VR has an important role in limiting skill fade.